THE AESTHETIC FUNCTION OF THE LANGUAGE - D.Turdaliyeva (International Engineering Journal For Research & Development, 2020)
The Uzbek people's proverbial dictionary contains no grease, no drool, no tea, no good, no goodness - a good thing, a good house, a rich house, a rich man, a good man. There are options for the mountains, until you get to the bay. The options given are also of significance. In order to analyze this line, it is desirable to clarify the matter of matter and transformant in the first place.